The physics of theism god, physics, and the philosophy of science - Koperski, Jeffrey (Hoboken, New Jersey Wiley/Blackwell, 2015)
Theologians and philosophers of religion have become increasingly interested in science, and especially in the area of physics. From the fine-tuning of universal constants to quantum mechanics, relativity, and cosmology, physics is a subject surprisingly widespread in its connection to the area of religion. Bridging the gap between these fields, however, has proven to be problematic; those in religion and the humanities typically interact with the mathematical sciences only at a popular level, and physicists are often dismissive of metaphysics and religion. The Physics of Theism offers a significant and necessary middle ground between these disciplines, presenting a critical analysis of the ways in which physics is intertwined within matters of religion. Bringing clarity to often complex arguments, Koperski covers a broad range of issues that include divine action, free will, the fine-tuning argument, naturalism, the laws of nature, the relation between science and religion, and the controversy over Intelligent Design. The text is ideal for both students and scholars, providing the appropriate level of explanation of arguments to provide a starting point for research, while at the same time delivering an important contribution to current scholarship.
Includes bibliographical references and index.
Keywords: Physics -- Religious aspects; Theism; Religion and science; Science -- Philosophy